Analysis of Reading Interest with the Role of The Library at MAN 8 Jombang - Moh Faridl Darmawan; Retno Dwi Maesya (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This study aims to determine the library management of MAN 8 Jombang based on the National Library Standard. This research is a qualitative research which was conducted at the Library of MAN 8 Jombang. The technique of taking research subjects used snowball sampling with a case study approach. Data collection was carried out by means of unstructured interviews, with the head of the library, employees or staff, and users of the MAN 8 Jombang library, observing the state or condition of the MAN 8 Jombang library, and relevant documents. The results of this study, among others, the Library of MAN 8 Jombang has library management, which includes buildings, collections of library materials, labor and services. Based on the National Library Standards, the area of ​​the MAN 8 Jombang library building still cannot be said to be effective, because the building is inadequate, besides that some rooms are in the MAN 8 Jombang building less than 5m2. Judging from the aspect of the number of library materials, the comparison of collections of general works or fiction books is 20% and non-fiction books related to the curriculum by 77%. The library of MAN 8 Jombang has not fulfilled the management of the library in the aspect of the library building which is not designed according to the needs of visitors with disabilities. In addition, MAN 8 Jombang still divides the focus or especially the budget on classes used for teaching and learning activities.